Kekurangan Energi Kronis Berhubungan dengan Kejadian Anemia pada Kehamilan Trimester I - Aprilia Ari Krisnawati; Endah Kusuma Wardani; Rima Nur Khasanah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Anemia in pregnancy is a condition of pregnant women with hemoglobin (Hb) levels <11 mg/dL in the first and third trimesters while in the second trimester Hb levels <10.5 mg/dL and can be a major cause of maternal and fetal morbidity and mortality. One of the causes of anemia in pregnancy is chronic energy deficiency (CED). This study aims to analyze the relationship between chronic energy deficiency and anemia in the first trimester of pregnancy. This research method is observational analytic with a cross-sectional design. The number of samples was 91 respondents with a total sampling technique. The independent variable is chronic energy deficiency. The dependent variable is anemia in pregnant women. The instrument used was a maternal cohort register. Data analysis used the Spearman Rank statistical test. The results of the study were obtained from 91 respondents who experienced chronic energy deficiency as many as 12 people. Of these, 7 mothers (58.3%) experienced anemia and 5 mothers (41.7%) did not experience anemia. Based on the results of the Spearman Rank statistical test, a significance value of 0.000 was obtained, a correlation coefficient of 0.590 with a positive direction, which means that there is a significant relationship between chronic energy deficiency and the occurrence of anemia in the first trimester of pregnancy with a fairly close relationship and a positive relationship direction. It is hoped that women of childbearing age will pay more attention to nutritional intake in order to prevent the occurrence of chronic energy deficiency as a cause of anemia during pregnancy.